The Selectivity of Buton Pot’s Escape Gap in Kotania Bay, Maluku, Indonesia - Tupamahu, Agustinus; Pailin, Jacobus B; Haruna, Haruna; Sangadji, Selfi (International Journal of Environment, Agriculture and Biotechnology, 2022)
This research was aimed at proving the differences between the catch results of fish trapped inside the bubu buton (fish pot) and those that escaped through the escape gap and to analyze the selectivity of the escape gap for the dominant trapped fish. This research was carried out in Kotania Bay in the period of March-May 2019 through fishing experiment. Five units of bubu buton with a dimension of 70x70x26 cm, containing 4 escape gaps in each unit, were used during the experiments carried out with a total of 11 trips. The results showed that there were 19 fish families caught during the study, dominated by Scaridae family. There was a significant difference between the weight of the trapped fish and those that escaped through the escape gap at the significance level of t_α0,05. Among the 19 families caught, the trapped percentage was different between the fish trapped inside the fish pot and those that escaped through the escape gap. The 50% trapped and escape chance (L50) of the Scaridae family from the escape gap was found in fish with a total length of 22.3 cm, which became the indication of sustainable management.